Association of Left Ventricular Global Longitudinal Strain with Exercise Capacity in Heart Failure with Preserved Ejection Fraction - Ljubica Georgievska-Ismail; Zarko Hristovski; Planinka Zafirovska (Official Publication of Rajaie Cardiovascular Medical and Research Center / Wolters Kluwer, 2017)
Background: Left ventricular global longitudinal strain (GLS) analysis using two-dimensional (2D) speckle-tracking echocardiography (STE) is a method for detecting subclinical systolic dysfunction. We hypothesized that exercise capacity (EC) is more closely related to systolic than diastolic dysfunction, especially to GLS in patients with heart failure and preserved ejection fraction (HFpEF). Methods: We assessed LV systolic and diastolic function in 172 patients with HFpEF using 2D echocardiography and STE. EC measured in units of metabolic equivalents (METs) was assessed using Bruce protocol treadmill stress testing. We defined reduced EC as <7 METs. Results: Out of 172 patients, 54 (31.4%) had EC of <7 METs. Patients with reduced EC of <7 METs versus those with ≥7 METs were significantly older (P = 0.0001), female (P = 0.001) with higher body mass index (BMI) (P = 0.001) and waist circumference for both man and women (P = 0.040, P = 0.001, respectively) as well as with higher resting heart rate (HR) (P = 0.009). Logistic regression analysis of EC as the dependent variable revealed that conventional risk factors (age, female gender, higher waist circumference, increased resting HR, and increased diastolic resting blood pressure) appeared as independent predictors of <7 METs. When age, gender, and hypertension were omitted from the analysis the results demonstrated that increased resting HR (odds ratio [OR] 1.025, P = 0.059, 95% confidence interval [CI] 0.997–1.192), higher BMI (OR 1.148, P = 0.003, 95% CI 1.047–1.258) along with elevated E/E’ average ratio (OR 1.090, P = 0.059, 95% CI 0.997–1.192) appeared as independent predictors of <7 METs. In addition, when we included only echocardiographic variables into the logistic model, the results showed that only lower GLS% (more positive) appeared as an independent predictor of <7 METs (OR 1.111, P = 0.044, 95% CI 1.003–1.231). Conclusion: Greater impairment of GLS in patients with HFpEF appeared as a significant independent predictor of reduced EC by METs achieved.
Keywords: exercise capacity; heart failure with preserved ejection fraction; left ventricular longitudinal strain; speckle tracking echocardiography